Regenerative Endodontics and Minimally Invasive Dentistry: Intertwining Paths Crossing Over Into Clinical Translation - Elnawam, Hisham; Abdelmougod, Menatallah; Mobarak, Ahmed; Hussein, Mai; Aboualmakarem, Hamdy; Girgis, Michael; El Backly, Rania (Frontiers in Bioengineering and Biotechnology, 2022)
Regenerative endodontic procedures have been described for over a decade as a paradigm shift in the treatment of immature necrotic permanent teeth, owing to their ability to allow root maturation with subsequent enhancement of the tooth’s fracture resistance in addition to the potential for regeneration of vital intracanal tissues. Concomitantly, minimally invasive endodontics is another rising concept with the main concern of preservation of tooth structure. Stemming from their potential to preserve the original tooth structure, both regenerative and minimally invasive endodontics could be considered as two revolutionary sciences with one common goal. Achieving this goal would entail not only employing the appropriate strategies to recreate the ideal regenerative niche but modifying existing concepts and protocols currently being implemented in regenerative endodontics to address two important challenges affecting the outcome of these procedures; conservation of tooth structure and achieving effective disinfection. Therefore, the search for new biomimetic cell-friendly disinfecting agents and strategies is crucial if such a novel integratory concept is to be foreseen in the future. This could be attainable by advocating a new merged concept of “minimally invasive regenerative endodontic procedures (MIREPs),” through modifying the clinical protocol of REPs by incorporating a minimally invasive access cavity design/preparation and biomimetic disinfection protocol, which could enhance clinical treatment outcomes and in the future; allow for personalized disinfection/regeneration protocols to further optimize the outcomes of MIREPs. In this review, we aim to introduce this new concept, its realization and challenges along with future perspectives for clinical implementation.